Corporate Sustainable Growth Among Listed Non-Financial Firms in Nigeria During Financial Crisis: Does Board Characteristics Matter? - Taiwo Olufemi Asaolu; Johnson Kolawole Olowookere; Aderemi Olalere Adebayo; Tajudeen Kareem (International Journal of Entrepreneurship and Sustainability Studies, 2023)
During the worldwide financial catastrophe and pandemic, non-financial firms faced several challenges. Corporate survival in these difficult times necessitates the agitation for the long-term growth of the companies. Sustainable growth is defined as growth witnessed by a company in a stand-alone position without any outside finance. Sustainability in a term of long-term growth is obtained through the existence of effective qualities of the board of directors. There is indeed the existence of fantastic research on the theme of our study. However, the studies were not only scanty, but they were of divergent results and did not cover all the countries. Against these loopholes, our study was conducted to investigate the influence of board qualities on the sustainable growth of non-financial firms in Nigeria. Listed firms other than financial ones on the Nigerian Exchange Group, between 2011 to 2020 were the population of the study. 60 companies were selected through the application of content analysis. The best multiple regression model adopted for the study, after the conduction of the Breusch-Pagan LM test and Hausmann test, was the random effect through e-view 8.0. The result obtained was that board qualities – size, independence, and meeting – had positive cum significant impacts on SGR (coefficients: 0.0659, 0.0405, 0.0508; p-values < 0.05). while board gender diversity was positively correlated with sustainable growth though insignificant at the 5% threshold of significance (coefficient: 0.0397; p-value > 5%). The study was in support of principal-agent theory because effective features of the board were seen to be a way of solving the principal-agent problem.